The McLaurys in Tombstone, Arizona : an O.K. Corral obituary - Johnson, Paul Lee, 1949- (A.C. Greene series, 2012)
On a chilly October afternoon in 1881, two brothers named Tom and Frank McLaury were gunned down on the streets of Tombstone, Arizona, by the Earp brothers and Doc Holliday. The deadly event became known as the gunfight at the O.K. Corral, and in a quirk of fate, the brothers' names became well-known, but only as bad men and outlaws. Did they deserve that reputation? The McLaurys in Tombstone, Arizona: An O.K. Corral Obituary explores this question, revealing details of their family background and the context of their lives on the frontier. Paul Lee Johnson begins their story with the McLaury brothers' decision to go into the cattle business with an ambition to have their own ranch. When they moved to Arizona, they finally achieved that goal, but along the way they became enmeshed with the cross-border black market that was thriving there. As "honest ranchers" they were in business with both the criminal element as well as the legitimate businesses in Tombstone. Another principal in this story was an older brother, William, who set aside his law practice in Fort Worth to settle his brothers' affairs, and associated himself with the prosecution of the Earp brothers and Doc Holliday. Despite his efforts, the Earps and Holliday were exonerated, and the "Gunfight at the O.K. Corral" became the opening salvo of a feud that took several more lives. Johnson has interviewed family descendants and mined their sources, government correspondence, and letters that have never before been published to reveal the human lives behind the storied events. For the first time the events of the O.K. Corral gunfight are presented from the viewpoint of the McLaurys, two brothers who lost their lives and reputations, and a family who tried in vain to find restitution